2015
DOI: 10.1016/j.cell.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Threonine Phosphorylation Regulates Asymmetric Histone Inheritance in the Drosophila Male Germline

Abstract: SUMMARY A long-standing question concerns how stem cells maintain their identity through multiple divisions. Previously we reported that pre-existing and newly synthesized histone H3 are asymmetrically distributed during Drosophila male germline stem cell (GSC) asymmetric division. Here we show that phosphorylation at Threonine 3 of H3 (H3T3P) distinguishes preexisting versus newly synthesized H3. Converting T3 to the unphosphorylatable residue alanine (H3T3A) or to the phosphomimetic aspartate (H3T3D) disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
126
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(159 citation statements)
references
References 57 publications
16
126
1
1
Order By: Relevance
“…Further investigation is required to test these ideas. Intriguingly, a similar phenomenon was recently reported in the Drosophila male germ line (48,49), where the germ line stem cells (GSCs) undergo asymmetric cell division to generate one GSC and one differentiating daughter cell. Chen and coworkers (48) discovered that old/pre-existing canonical histone H3 but not H3.3 were selectively segregated to the daughter GSC.…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 91%
See 2 more Smart Citations
“…Further investigation is required to test these ideas. Intriguingly, a similar phenomenon was recently reported in the Drosophila male germ line (48,49), where the germ line stem cells (GSCs) undergo asymmetric cell division to generate one GSC and one differentiating daughter cell. Chen and coworkers (48) discovered that old/pre-existing canonical histone H3 but not H3.3 were selectively segregated to the daughter GSC.…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 91%
“…Chen and coworkers (48) discovered that old/pre-existing canonical histone H3 but not H3.3 were selectively segregated to the daughter GSC. They further showed that H3T3ph was required for the asymmetric inheritance of H3, and they suggested it was required in a specific time window (prophase to metaphase) (49). The asymmetric cell division is only limited to Drosophila GSCs and is not seen in surrounding somatic tissues, so is the asymmetric distribution of H3T3ph and directional inheritance of histone H3 (48,49).…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sp100C Tolerates and Recognizes H3T3 PhosphorylationH3T3ph is a hallmark of chromosome segregation and contributes to asymmetric histone inheritance (25) as well as heritable epigenetic silencing (26). There exists a basic residue, Arg 713 , in the vicinity of H3T3 (Fig.…”
Section: Mutagenesis and H3k4me0 Co-localization Analysis-mentioning
confidence: 99%
“…Noteworthy, newly synthesized histones H3 undergo a delay in mitotic phosphorylations associated with chromosome condensation, as shown in Drosophila and human cells. 24,25 We could then envision that the incorporation of new histones during DNA damage repair could interfere with chromosome condensation in early mitosis and thus serve as a "chromatin checkpoint" mechanism ensuring that incompletely repaired material cannot be transmitted to the next cell generation.…”
Section: Recovery Of Parental Histones In Repairing Chromatinmentioning
confidence: 99%